CADEIAS REFERENCIAIS NO PORTUGUÊS FALADO - Costa, Iara Bemquerer (Organon, 2012)
This paper aims at identifying the set of factors which determine thechoice among alternative forms of remissive references in spoken Portuguese. Forthat purpose, we analysed 100 texts extracted from recordings of oral enterviews,of which 50 are narrative and 50 argumentative. The empirical analysis of theforms used to express co-referenciality indicates that the most relevant factordetermining the selection of a specific form is the distinction between animate andinanimate referents.